2010
DOI: 10.1007/s00208-010-0529-z
|View full text |Cite
|
Sign up to set email alerts
|

On the dimension of divergence sets of dispersive equations

Abstract: We refine results of Carleson, Sjögren and Sjölin regarding the pointwise convergence to the initial data of solutions to the Schrödinger equation. We bound the Hausdorff dimension of the sets on which convergence fails. For example, with initial data in H 1 (R 3 ), the sets of divergence have dimension at most one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
95
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(100 citation statements)
references
References 37 publications
5
95
0
Order By: Relevance
“…The bound is best possible in one dimension, in which case the central intervals are empty and the dimension jumps by a half over s = 1/4. This is a consequence of the Dahlberg-Kenig example combined with [1], where it was proven that α n (s) ≤ n − 2s in the range n/4 ≤ s ≤ n/2. For the best known upper bounds with lower regularity, see [14,Theorem 1.2].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The bound is best possible in one dimension, in which case the central intervals are empty and the dimension jumps by a half over s = 1/4. This is a consequence of the Dahlberg-Kenig example combined with [1], where it was proven that α n (s) ≤ n − 2s in the range n/4 ≤ s ≤ n/2. For the best known upper bounds with lower regularity, see [14,Theorem 1.2].…”
Section: Introductionmentioning
confidence: 94%
“…In order to understand the behaviour of e i t 2πR ∆ f θ we first consider the unmodulated version e i t 2πR ∆ g. Barceló, Bennett, Carbery, Ruiz and Vilela [2] showed that 1 We write a b (a b) whenever a and b are nonnegative quantities that satisfy a ≤ Cb (a ≥ Cb) for a constant C > 0. We write a ≃ b when a b and b a.…”
Section: Proof Of the Lebesgue Measure Necessary Conditionmentioning
confidence: 99%
“…Indeed, recalling (99) and summing over N , this would imply the validity of (94), (95), (96) for this term. We could have required a weaker bound than (102), replacing the X 0+, 1 2 + δ norm with an X α+σ, 1 2 + δ norm if J 2 = II and with a (− ln ε) factor if J 2 = I. However, we are able to prove the stronger estimate (102).…”
mentioning
confidence: 90%
“…In this work, we are concerned with the question of almost everywhere convergence of solutions to the nonlinear Schrödinger equation (NLS) to initial data. More precisely, let u(x, t) be a solution to (1) i∂ t u + ∆u = N (u), u(x, 0) = f (x),…”
mentioning
confidence: 99%
See 1 more Smart Citation